Orthomosaic, Digital Elevation Model (DEM) and textured 3D Model of the White Seal-Hound hydrothermal vent in the Aegean Sea, from ROV SQUID dive videos, RV METEOR Expedition M192/2 - Yann Marcon; Solveig I Bühring (PANGAEA, 2025)
In 2023, expedition M192-2 aboard the RV METEOR discovered the White Seal-Hound hydrothermal structure. This unique feature is a positive seafloor structure, formed by shallow-water hydrothermal activity, located at approximately 185 meters water depth. Unlike deep-sea chimneys, such as white and black smokers, which rise vertically in the water column, the White Seal-Hound structure is a prominent overhang, predominantly white in colour and resembling a seal with the head of a floppy-eared dog. The White Seal-Hound structure was discovered and filmed during dive 75 of the ROV SQUID (MARUM) on 26 August 2023. Using photogrammetry techniques (Arnaubec et al., 2023, https://doi.org/10.3390/jmse11050985), we reconstructed a 3D model of the structure and its surroundings from the ROV dive videos.